2018
DOI: 10.24940/ijird/2018/v7/i8/aug18054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Consumer Price Index and Gross Domestic Saving on Economic Growth in Sri Lanka: An Econometric Analysis Using Johansen Co-Integration Approach

Abstract: Introduction One of the important contributors to economic growth is Gross domestic product (GDP). The GDP is a monetary measure of the market value of all final goods and services produced in a specific period of time. Contemporary, the Sri Lankan economy has revealed a robust raising trend with per capita GDP reaching almost $4,000. Sri Lankan government has been implementing privatization and an open economy for worldwide competition which inspiring overseas investments from 1977. Resulting to the controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This is different from Lamah, Yanto and Setyadharma (2021) who found that CPI has no significant influence in Indonesian economy at all. However, the result suggests that CPI can speed up the economic growth via gross domestic saving (GDS) (Aboobucker & Jahufer, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This is different from Lamah, Yanto and Setyadharma (2021) who found that CPI has no significant influence in Indonesian economy at all. However, the result suggests that CPI can speed up the economic growth via gross domestic saving (GDS) (Aboobucker & Jahufer, 2018).…”
Section: Resultsmentioning
confidence: 99%